Ownership Succession: Plan Now for the Future of Your Land - Chris Demers (EDIS)
FOR-212, a 4-page fact sheet by Chris Demers, outlines 8 steps for forestland owners to set up a smooth transition between themselves and the future owners of their property. Includes references. Published by the UF School of Forest Resources and Conservation, March 2009.